Characterization of a phospholipase D from Streptomyces cinnamoneum SK43.003 suitable for phosphatidylserine synthesis. (17th October 2021) - Li, Mengli; Zhou, Yanfeng; Duan, Xiaoli; Zhou, Licheng; Zhang, Tao
Abstract: A phospholipase D high producing strain with transphosphatidylation activity that is suitable for phosphatidylserine synthesis was screened by our laboratory and named as Streptomyces cinnamoneum SK43.003. The enzyme structural and biochemical properties were investigated using the molecular biology method. A 1521‐bp fragment of the phospholipase D gene from Streptomyces cinnamoneum SK43.003 was amplified by PCR and encoded for 506 amino acids. The primary structure contained two conserved HKD and GG/S motifs. The pld gene was cloned and expressed in Escherichia coli . The purified enzyme exhibited the highest activity at a pH value of 6.0 andtemperature of 60°C. The enzyme was stable within a pH range of 4–7 for 24 h or at temperatures below 50°C. In addition, Triton X‐100, Fe 2+, and Al 3+ were beneficial to the enzyme activity, whereas Zn 2+ and Cu 2+ dramatically inhibited its activity. In a two‐phase system, the enzyme could convert phosphatidylcholine to phosphatidylserine with a 92% transformation rate. Abstract : A phospholipase D from Streptomyces cinnamoneum SK43.003 for phosphatidylserine synthesis